Indirect determination of some analgesic-inflammatory drugs by AAS - Alpdogan, G; Sungur, S (MARCEL DEKKER INC, 1999)
An Indirect AAS method has been developed for the determination of analgesic-inflammatory drugs, mefenamic acid, flufenamic acid and diclofenac sodium. The method depends on the complexation with copper (II) ammine sulphate. The complex was extracted into chloroform and the concentrations of substances were determined indirectly by AAS measurement of copper, after reextraction into 0.3 N nitric acid solution. The developed method was applied to the assay of the drug substances in commercial tablet formulations. The results were statistically compared with those obtained by HPLC method by t- and F-tests at 95% confidence level. Calculated t and F values were both lower than the table values.
Keywords: mefenamic acid; flufenamic acid; diclofenac sodium; atomic absorption spectrophotometry; NONSTEROIDAL ANTIINFLAMMATORY DRUGS; SPECTROPHOTOMETRIC DETERMINATION; PHARMACEUTICAL PREPARATIONS; ACID; TLC; Chemistry